2021
DOI: 10.1038/s41467-020-20752-6
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 mutations induce organelle defects via dysregulated phospholipids

Abstract: Infiltrating gliomas are devastating and incurable tumors. Amongst all gliomas, those harboring a mutation in isocitrate dehydrogenase 1 mutation (IDH1mut) acquire a different tumor biology and clinical manifestation from those that are IDH1WT. Understanding the unique metabolic profile reprogrammed by IDH1 mutation has the potential to identify new molecular targets for glioma therapy. Herein, we uncover increased monounsaturated fatty acids (MUFA) and their phospholipids in endoplasmic reticulum (ER), genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…IDH1 is an isocitrate dehydrogenase enzyme found in the cytoplasm as well as on peroxisomes that catalyzes the reversible oxidative decarboxylation of isocitrate to alpha-ketoglutarate 30 . Loss-of-function mutations in human IDH1 lead to increased monosaturated fatty acids and increased SCD expression in infiltrating gliomas 31 . Since there is increased eyecup Scd1 expression in Tmem135 FUN025 / FUN025 mice and SCD1 is the rate-limiting enzyme for the conversion of saturated fatty acids to monounsaturated fatty acids 32 , the increased Idh1 expression in Tmem135 FUN025 / FUN025 mouse eyecups may occur to decrease the amount of monounsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…IDH1 is an isocitrate dehydrogenase enzyme found in the cytoplasm as well as on peroxisomes that catalyzes the reversible oxidative decarboxylation of isocitrate to alpha-ketoglutarate 30 . Loss-of-function mutations in human IDH1 lead to increased monosaturated fatty acids and increased SCD expression in infiltrating gliomas 31 . Since there is increased eyecup Scd1 expression in Tmem135 FUN025 / FUN025 mice and SCD1 is the rate-limiting enzyme for the conversion of saturated fatty acids to monounsaturated fatty acids 32 , the increased Idh1 expression in Tmem135 FUN025 / FUN025 mouse eyecups may occur to decrease the amount of monounsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that IDH1mut induced altered lipid metabolism. Doxycycline–driven IDH1mut overexpression in U251 impaired the PUFAs contents in endoplasmic reticulum and golgi [ 30 ] and cholesterol homeostasis [ 31 ], suggesting altered intracellular lipid contents may affect the localization and expression of FABP7. Furthermore, there may be a difference in the therapeutic target is different between IDH1wt and IDH1mut glioma considering the different lipid metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Its signal also shows an intensity that is linearly proportional to the concentration of the targeted molecules and is free of nonresonant background. With the intensity of the signal proportional to the concentration of the metabolites of interest, semi-quantitative molecular profiling of single cells and tissues is possible [23][24][25][26][27]. SRS would be a complementary tool to spontaneous Raman scattering and simultaneously using the two can be beneficial (Table 1) [28].…”
Section: Coherent Raman Scattering For High-speed Imagingmentioning
confidence: 99%